FOLLOWING THE TRACES OF NAXIAN EMERY – AN IMPLEMENTATION OF ENVIRONMENTAL EDUCATION IN GEODIDACTICS - Kritikou, S.; Malegiannaki, I. (Bulletin of the Geological Society of Greece, 2010)
During the school year 2007-08 the environmental team of Naxos 2nd Junior High school accomplished the project entitled “Following the traces of naxian emery”. The emery related topic was chosen due to the great importance of this mineral to the island’s life and geoenvironment. The main purpose of this project was to inform the students and also a broader public, outside Naxos, about emery - a material that played, since antiquity, a significant role in naxian society and culture, and Greek history in general. The project also intended to sensitize the students and the local community relatively to the sustainable development of regions that suffer of population and cultural decline. In a framework of research and artistic creation, the team created educational material concerning the emery issue, which is available to other schools – “The emery educational kit”. This consisted of a) an information booklet concerning the stone, b) a puzzle game relative to emery mining, c) an educational board game about emery and d) a documentary film produced by the team and entitled “Following the traces of naxian emery”.